Mutant p53 accumulation in human breast cancer is not an intrinsic property or dependent on structural or functional disruption but is regulated by exogenous stress and receptor status. Issue 3 (21st May 2014) - Bouchalova, Pavla; Nenutil, Rudolf; Muller, Petr; Hrstka, Roman; Appleyard, M Virginia; Murray, Karen; Jordan, Lee B; Purdie, Colin A; Quinlan, Philip; Thompson, Alastair M; Vojtesek, Borivoj; Coates, Philip J
Abstract Many human cancers contain missense TP53 mutations that result in p53 protein accumulation. Although generally considered as a single class of mutations that abrogate wild‐type function, individual TP53 mutations may have specific properties and prognostic effects. Tumours that contain missense TP53 mutations show variable p53 stabilization patterns, which may reflect the specific mutation and/or aspects of tumour biology. We used immunohistochemistry on cell lines and human breast cancers with known TP53 missense mutations and assessed the effects of each mutation with four structure–function prediction methods. Cell lines with missense TP53 mutations show variable percentages of cells with p53 stabilization under normal growth conditions, ranging from approximately 50% to almost 100%. Stabilization is not related to structural or functional disruption, but agents that stabilize wild‐type p53 increase the percentages of cells showing missense mutant p53 accumulation in cell lines with heterogeneous stabilization. The same heterogeneity of p53 stabilization occurs in primary breast cancers, independent of the effect of the mutation on structural properties or functional disruption. Heterogeneous accumulation is more common in steroid receptor‐positive or HER2‐positive breast cancers and cell lines than in triple‐negative samples. Immunohistochemcal staining patterns associate with Mdm2 levels, proliferation, grade and overall survival, whilst the type of mutation reflects downstream target activity. Inhibiting Mdm2 activity increases the extent of p53 stabilization in some, but not all, breast cancer cell lines. The data indicate that missense mutant p53 stabilization is a complex and variable process in human breast cancers that associates with disease characteristics but is unrelated to structural or functional properties. That agents which stabilize wild‐type p53 also stabilize mutant p53 has implications for patients with heterogeneous mutant p53 accumulation, where therapy may activate mutant p53 oncogenic function. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.